Fatigue Index Analysis in Student Soccer Clubs after 45 Minutes of Soccer Match - S, Wedi; Sinulingga, Andrew Rinaldi (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
The purpose of this study was to determine and see the value of the fatigue index in student football athletes after playing a match for 45 minutes in the first halfs. This study used a quantitative descriptive method with 22 sample. The instrument used in this study is the Running-based Anaerobic Sprint Test (RAST), which is a test carried out by sprinting with a distance of 35 meters for 6 repetitions and a 10 second rest interval for each repetition performed by the athlete. The test results showed that from 22 students who played soccer for 45 minutes, 15 students (68.18%) had a high fatigue index value, while 7 students (31.82%) had a low fatigue index value. Based on the results of data analysis and discussion, it can be concluded that 15 out of 22 people (68.18%) of student soccer athletes after playing a soccer match for 45 minutes in the first half had a high fatigue index value.